2010
DOI: 10.14314/polimery.2010.379
|View full text |Cite
|
Sign up to set email alerts
|

Rheological studies of highly-filled polyolefinic composites taking into consideration p-v-T characteristics

Abstract: Badania reologiczne kompozytów poliolefinowych o wysokim stopniu nape³nienia z uwzglêdnieniem charakterystyk p-v-T * *) Streszczenie-W czêoeci wstêpnej publikacji podano obszern¹ ogóln¹ charakterystykê nape³niaczy oraz omówiono mo¿liwooeci ich modyfikacji i jej wp³yw na w³aoeciwooeci uzyskiwanych z nich kompozytów. Przedstawiono wyniki w³asnych pomiarów reologicznych wysokonape³nionych (48-64 % mas.) kompozytów poliolefinowych, w których nape³nienie stanowi³ wêglan wapnia wprowadzany w postaci koncentratu i-PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…For the polypropylene only 5.54 3 10 3 PaÁs. The drop in viscosity is the result of the increase in the contents of the iPP and CaCO 3 modifiers that is, stearic acid and waxes, in the system, as has been reported by the authors of the publication [30,38]. The behaviors of the viscosity curves determined for the reference curves have confirmed the previous MFR variation results.…”
Section: Resultssupporting
confidence: 85%
“…For the polypropylene only 5.54 3 10 3 PaÁs. The drop in viscosity is the result of the increase in the contents of the iPP and CaCO 3 modifiers that is, stearic acid and waxes, in the system, as has been reported by the authors of the publication [30,38]. The behaviors of the viscosity curves determined for the reference curves have confirmed the previous MFR variation results.…”
Section: Resultssupporting
confidence: 85%
“…Rheological properties tests by using the devices previously described are off‐line measurements. There is also possibility to evaluate the viscosity of plasticized polymer materials on‐line or in‐line . It should be noted, however, that the first two research methods (by using plastometer and rheometer) do not comply all phenomena that occur in the plasticizing system of processing machines.…”
Section: Introductionmentioning
confidence: 99%
“…There is also possibility to evaluate the viscosity of plasticized polymer materials on-line or in-line. [4][5][6][7] It should be noted, however, that the first two research methods (by using plastometer and rheometer) do not comply all phenomena that occur in the plasticizing system of processing machines. Friesenbichler has showed that the viscosity measured by a capillary rheometer differs by 10% from the value determined during injection molding.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to different statements regarding the influence of calcium carbonate on thermal properties and crystallinity degree of polyethylene and polypropylene, the main task of our studies was to determine the influence of CaCO 3 and its surface modification on nonisothermal crystallization of highly‐filled polyolefin composites (HFPCs). The HFPCs are ternary composites (PE‐MD/iPP/CaCO 3 ) that may be used in the production of paper‐like films …”
Section: Introductionmentioning
confidence: 99%
“…The HFPCs are ternary composites (PE-MD/iPP/CaCO 3 ) that may be used in the production of paper-like films. 27,28 One of the most significant difficulties occurring in the production of oriented materials, like films and fibers, is early viscosity increase caused by additives acting as nucleating agents on the semicrystalline polymeric matrix. In case of highly-filled composites (that contain between 30 and 50 wt % of the filler) designated for cast film production, the evaluation of crystallization kinetics, especially during primary crystallization, is necessary.…”
Section: Introductionmentioning
confidence: 99%